Inhibiting Heat Shock Protein 90 Protects Nucleus Pulposus-Derived Stem/Progenitor Cells From Compression-Induced Necroptosis and Apoptosis - Hu, Binwu; Zhang, Shuo; Liu, Weijian; Wang, Peng; Chen, Songfeng; Lv, Xiao; Shi, Deyao; Ma, Kaige; Wang, Baichuan; Wu, Yongchao; Shao, Zengwu (Frontiers in Cell and Developmental Biology, 2020)
Nucleus pulposus-derived stem/progenitor cells (NPSCs) provide novel prospects for the regeneration of degenerated intervertebral disc (IVD). Nevertheless, with ageing and degeneration of IVD, the frequency of NPSCs markedly decreases. Excessive cell death could be the main reason for declined frequency of NPSCs, however, the exact mechanisms remain elusive. Thus, the present study was undertaken to explore the mechanisms of compression-induced NPSCs death, and the effects of heat shock protein 90 (HSP90) on NPSCs survival. Here, we found that compression could trigger receptor-interacting protein kinase 1 (RIPK1)/receptor-interacting protein kinase 3 (RIPK3)/mixed lineage kinase domain-like protein (MLKL)-mediated necroptosis of NPSCs. Furthermore, we found that elevated expression of HSP90 was involved in compression-induced NPSCs death, and inhibiting HSP90 could dramatically attenuate compression-induced necroptosis of NPSCs via regulating the expression and activity of RIPK1/RIPK3/MLKL, and alleviating the mitochondrial dysfunction (mitochondrial membrane potential loss and ATP depletion) and oxidative stress (production of mitochondrial reactive oxygen species (ROS), cellular total ROS and malondialdehyde, and downregulation of superoxide dismutase 2). Besides necroptosis, compression-induced apoptosis of NPSCs was also attenuated by HSP90 inhibition. In addition, we found that enhanced expression of HSP70 contributed to the cytoprotective effects of inhibiting HSP90. More encouragingly, our results demonstrated that inhibiting HSP90 could also mitigate the exhaustion of NPSCs in vivo. In conclusion, RIPK1/RIPK3/MLKL-mediated necroptosis participates in compression-induced NPSCs death. Furthermore, targeting HSP90 to simultaneously inhibit necroptosis and apoptosis of NPSCs might be an efficient strategy for preventing the death of NPSCs, thus rescuing the endogenous repair capacity of NP tissue.